Efforts to Improve the Ability to Read and Write the Qur'an of Elementary Madrasah Students - Somantri, Somantri; Arief Muhammad Nurhasan; Aini, Qurotul; Puranti, Ayu (EduBase : Journal of Basic Education, 2025)
Objective: This research aims to analyze the efforts made to improve students' ability to read and write the Al-Qur'an at MI Darul Hikam. Novelty: The study highlights the specific strategies implemented by MI Darul Hikam, emphasizing the integration of iqra’ and tahfiz methods, which have not been extensively documented in similar contexts. Methods: The research method was carried out using a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. Results: The research results show that MI Darul Hikam implemented various strategies to improve these abilities, including the use of iqra’ and tahfiz methods. This can be seen from the existence of a well-implemented Al-Qur'an (BTQ) reading and writing program and the use of appropriate methods, intensive guidance programs, as well as support from the school and parents. Conclusion: As a result of these efforts, students' ability to read and write the Al-Qur'an experienced a significant increase.